Altered Gut Microbiota and Compositional Changes in Firmicutes and Proteobacteria in Mexican Undernourished and Obese Children - Méndez-Salazar, Eder Orlando; Ortiz-López, María Guadalupe; Granados-Silvestre, María de los Ángeles; Palacios-González, Berenice; Menjivar, Marta (Frontiers in Microbiology, 2018)
Mexico is going through an epidemiological and nutritional transition that affects children who bear a double burden of malnutrition, including undernutrition and obesity (16.2%, and 14.8% respectively). The gut microbiome is a complex and metabolically active community that influences its host’s phenotypes. Although previous studies have shown an altered gut microbiota composition in undernourished children, it is still unknown which bacterial communities are involved. The aim of the present study was to describe and compare the bacterial richness and diversity in fecal microbiota of undernourished (n=12), obese (n=12), and normal-weight (n=12) Mexican school-age children, using Next-Generation Sequencing to analyze the V3-V4 region of bacterial 16S rRNA gene, as well as examine the correlation between diet and relevant bacteria. Undernutrition and obesity groups showed lower bacterial richness and diversity than normal-weight group. Likewise, the Western diet can be identified in both groups through the enterotypes. The results showed that undernourished children have a significantly higher amount of Firmicutes phylum and Lachnospiraceae family than obese children, while the phylum Proteobacteria are overrepresented in the obese group. Also, Lachnospiraceae was negatively correlated with energy consumption. Thus, our data suggest that Lachnospiraceae could constitute a turning point that may lead to an increased risk of obesity later in life among undernourished children.